A new 3D heterometallic coordination polymer: luminescent property and nursing application value on acute cerebral infarction. Issue 1 (31st December 2022) - Cong, Li; Pan, Yun-Zhi; Qin, Ying-Hui; Jiang, Ji-Na
ABSTRACT: With the solvothermal reactions of flexible tetracarboxylic acid ligand with the Cd(II) and Ca(II) ions, we acquired a new heterometallic coordination polymer formulated as {[Cd2 Ca2 (L)2 (DMF)2 (H2 O)7 ]·(DMF)·2(H2 O)}n (1, H4 L is 5-(bis(4-carboxybenzyl)amino)isophthalic acid, DMF is N, N'-Dimethylformamide). Furthermore, the solids of 1 shows ligand-centered luminescence at room temperature. It not only evaluated the treatment and nursing application value on acute cerebral infarction, but also explored the related mechanism. Above of all, ELISA assay measured the content of the MMP-9 released into the cerebrospinal fluid, and the real time RT-PCR was implemented and the NF-κB activation in the brain tissue was measured.